Advances in business statistics, methods and data collection - Snijkers, Ger, 1963- (John Wiley & Sons, Inc., 2023)
"The latest developments in the production of business statistics, methods, and data collection In Advances in Business Statistics, Methods and Data Collection, distinguished researcher Dr. Ger Snijkers delivers an invaluable collection of new issues in business statistics, as well as its methods, and in the collection of business data. This edited volume offers new developments in business surveys--including discussions of non-probability sampling and web surveys--and statistical process control, the use of secondary data sources, register methodology, and possibilities presented by the Internet of Things. The included works present some of the most innovative and impactful developments in the optimization of the development, conduct, and evaluation of modern business programs. These include advancements in big data, machine learning, and advanced visualization. Providing a broad overview of the most up-to-date changes in business statistics and data, this book challenges the status quo and prepares researchers for future challenges"--